Characterization and risk stratification of coronary artery disease in people living with HIV: a global systematic review - Nweke, Martins; Ibeneme, Sam; Pillay, Julian D.; Mshunqane, Nombeko (Frontiers in cardiovascular medicine, 2025)
Coronary artery disease (CAD) is a leading cause of mortality among people living with HIV (PLWH). Risk stratification remains inconsistent due to geographic disparities, ART-related metabolic effects, and overreliance on strength of association. This review synthesizes global evidence to classify CAD risk factors in PLWH, aiming to improve predictive models and preventative strategies. Following the PRISMA 2020 guidelines, a systematic review was conducted across six databases: PubMed, Scopus, Web of Science, Medline, CINAHL, and African Journals (SABINET). Two independent reviewers screened studies and extracted data. Narrative synthesis and meta-analysis were conducted. Risk factors were classified using Rw, causality index (CI), and public health priority (PHP). Twenty-two studies involving 103,370 participants were included. First-class risk factors (CI: 7-10) included hypertension (OR: 4.9; < 0.05; Rw: 4.5), advanced age (≥50 years) (OR: 4.96, < 0.05, Rw: 3.58), dyslipidemia (OR: 2.15, < 0.04, Rw: 2.15), and overweight/obesity (OR: 1.81, < 0.05, Rw: 1.36). Second-class risk factors (CI: 5-6) included family history of CVD (OR: 3.25, < 0.05; Rw: 2. 24). Third-class risk factors (CI ≤4) included diabetes (OR: 2.64, < 0.05, Rw: 1.32), antiretroviral therapy exposure (OR: 1.68, < 0.05, Rw: 0.63), and homosexuality (OR: 1.82, < 0.05, Rw: 0.62). Critical thresholds (cumulative Rw: 14.8 and 8.0) were set at 75th and 50th percentiles of cumulative Rw. At GTT value of 0.50, the parsimonious global clinical prediction model for HIV-related CAD included age, hypertension, dyslipidemia, family history of CVD, diabetes, and overweight/obesity (Rw: 15.5, GTT: 4.05). For primary prevention, the optimal model comprised hypertension, dyslipidemia, and obesity (Rw: 8.01, GTT: 2.07). Advanced age and hypertension were "necessary causes" of CAD among PLWH. Association strength alone cannot determine CAD risk. Cumulative risk indexing and responsiveness provide a robust framework. Prevention should prioritize hypertension and dyslipidemia management, with interventions for obesity, smoking, and virological failure. Age and hypertension should prompt cardiovascular screening. Standardized risk definitions, accounting for the role of protective factors and integrating evidence with domain knowledge are vital for improved CAD risk stratification and prediction in PLWH. Routine cardiovascular screening in HIV care remains essential. https://www.crd.york.ac.uk/PROSPERO/view/CRD42024524494, PROSPERO CRD42024524494.